2022
DOI: 10.1136/bmjresp-2022-001295
|View full text |Cite
|
Sign up to set email alerts
|

COPD disease knowledge, self-awareness and reasons for hospital presentations among a predominately Indigenous Australian cohort: a study to explore preventable hospitalisation

Abstract: BackgroundThe prevalence of chronic obstructive pulmonary disease (COPD) is higher among Indigenous Australians than that of non-Indigenous Australians. However, no studies have investigated COPD disease awareness and knowledge among Indigenous Australians. In this study, we assessed the COPD disease awareness among Indigenous and non-Indigenous patients in the Top End Health Service region of the Northern Territory of Australia.MethodsOf a total convenience sample of 100 adults, 86 patients consented to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Of the 18 studies which reported on asthma (including the three studies which combined asthma and COPD),15 37 38 3 reported community cross-sectional data,35 36 39 2 reported on pregnant women,31 32 7 reported on patients from a hospital cohort,37 38 40–44 and 6 reported on patients referred to the respiratory health service (table 1). 7 14 15 30 45 46…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 18 studies which reported on asthma (including the three studies which combined asthma and COPD),15 37 38 3 reported community cross-sectional data,35 36 39 2 reported on pregnant women,31 32 7 reported on patients from a hospital cohort,37 38 40–44 and 6 reported on patients referred to the respiratory health service (table 1). 7 14 15 30 45 46…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used self-reported asthma to define prevalence,35 36 39 one used a combination of self-report and hospital admissions data,32 one used bronchodilator response (BDR),46 one used either BDR or electronic medical records (EMR) documentation for the presence of asthma44 and the remaining 12 used hospital admissions or entries on patients’ EMR 7 14 15 30 31 37 38 40–43 45. Excluding the three studies which combined COPD and asthma, and potentially overlapping studies, the average prevalence of asthma was 15.4% 30–32 35 36 39 42 46.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 , 6 A recent study from our center found that only seven percent of Indigenous patients and 30% of non-Indigenous patients with COPD could accurately describe their respiratory condition, although 46 and 89%, respectively, were aware that “something” was wrong with their lungs. 69 In the same study, 80% of Indigenous patients described shortness of breath, 60% described a cough and 10% described wheezing – thus it is easy to see how Indigenous patients may self-report a previous diagnosis of “asthma” in the presence of another underlying respiratory condition. When excluding the presence of COPD in the present study (via either radiology or spirometry), the prevalence of BDR dropped from 17% to 5% among Indigenous patients and from 13% to 7% among non-Indigenous patients (using the usual/traditional ≥12% and ≥0.2L criteria).…”
Section: Discussionmentioning
confidence: 95%